SISTEM INFORMASI PENJUALAN BAJU BATIK BERBASIS WEB PADA BUTIK DANISWARA BULUKUMBA - Nurlaelah Nurlaelah; Dedy Hendryadi; Nurwahid Syam (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to: (1) design a web-based information system for selling batik clothes at Daniswara Boutique Bulukumba. (2) implementing a web-based sales information system at the Bulukumba Daniswara Boutique. This research uses the waterfall method is a software development method with a linear sequential model, starting from the system requirements analysis, design, coding to the testing stage. This method has stages, namely: (1) Requirements analyst, (2) Design, (3) Implementation (Build & Coding), (4) Integration and Testing (Integration & testing), (5) Operation and Maintenance (Operation & maintenance). Based on the results of research on the web-based information system for selling batik clothes, it can be concluded that: (1) The web-based batik clothing sales system was built using Sublime software (text editor), MySQL Xampp 7 Database Management System (DBMS) uses the waterfall method and with the PHP programming language. (2) The batik shirt sales system consists of 2 users, namely Admin and Buyer. Based on the test, it was found that the web-based batik clothing sales information system can be used to facilitate data entry of goods, and make it easier for buyers to see the available categories of goods and can meet the needs of the user to select the desired item category.